Increased resistance to the convulsive effects of penthylenetetrazol in the hyperammonemic dogs with hepatic failure - Baydas, G.; Donder, E.; Akyol, A.; Baydas, B.; Naziroglu, M.; Celebi, H. (My University, 1996)
To evaluate the effect of ammonia on convulsions, 16 dogs were used. Model epilepsies were developed in all dogs by cortical destruction and by intracortical aluminum gel injection. Intravenous penthylenetetrazol (PTZ) were given to develop convulsions. After seven days, hepatocellular necrosis were induced by thioacetamid injection. After ammonia infusion, PTZ induced convulsion (PTZ-IC) levels were measured. Also, serum levels of zinc, ammonia, and gamma aminobutyric acid (GABA) were determined. After ammonia and zinc infusion, serum GABA was increased and PTZ-IC levels were slightly decreased in the dogs with hepatic failure but PTZ-IC levels were markedly decreased in dogs which received only zinc than in dogs which received both zinc and ammonia. In conclusion, after infusion of ammonium to the dogs with liver failure, there is a resistance to the convulsive effect of PTZ and zinc probably due to the increasing GABA-ergic tone.
Keywords: ammonia; epilepsy; GABA; hepatic encephalopathy